ISOLATION AND MOLECULAR STUDY OF SOME BACTERIAL URINARY TRACT INFECTIONS OF SHEEP IN BASRAH PROVINCE - & et al., Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed isolation and molecular detection of some causative agents of urinary tract infection (cystitis and pyelonephritis). Out of 108 tested urine samples (56 from females and 52 from males); 60 samples (55.55%) have infected with Escherichia coli and Klebsiella pneumoniae were 36 (64.2%) females and 24 (46.1%) males. The sixty infected samples contain from 56 E. coli and (4) K. pneumoniae, this samples identified by Vitek 2 (44 isolates E. coli and 2 isolates K. pneumoniae) were subjected to DNA extraction. A total of 44 E. coli isolates detected to FimH and pai genes. 44/44 (100%) were positive for presence of FimH gene, and 20/44 (45.45%) were positive for presence of pai gene. The two isolates of K. pneumoniae which detection of Ecpa gene and given positive result to this gene 100%.